Job creation in Italy: Geography, determinants and perspectives - Giovanni Peri; Alejandro Cu\~nat (Hamburg Institute of International Economics (HWWA), 2001)
The extremely large disparities in employment rates across Italian regions, and the bad performance of the Italian economy in terms of job creation in the 80s and early 90s make job creation a top-priority in the economic policy agenda. This paper uses data on employment from 784 Local Labor Systems (LLSs) covering the whole Italian territory to analyze job creation and its covariates for the 1981-1996 period. Local agglomeration economies, in particular input-output linkages, social characteristics, in particular the crime rate, and infrastructure growth are found to be important determinants of employment growth across Italian LLSs. Using these estimates and data relative to 1996, we assess the potential for job creation in the LLSs for the next decade. The Northeast still proves to be the area with strongest potentials, while in the South Abruzzi and Northern Campania are the areas best equipped for filling their gap with the North.
Keywords: O1; R3; R0; 330; Local Agglomeration Economies; Employment Growth; Italian Regions; Regionaler Arbeitsmarkt; Agglomerationseffekt; Industriestandort; Standortfaktor; Beschäftigungseffekt; Räumliche Verteilung; Schätzung; Italien